Magnetic versus crystal field linear dichroism in NiO thin films - Haverkort, Maurits W. (Arxiv, 2003)
We have detected strong dichroism in the Ni $L_{2,3}$ x-ray absorption spectra of monolayer NiO films. The dichroic signal appears to be very similar to the magnetic linear dichroism observed for thicker antiferromagnetic NiO films. A detailed experimental and theoretical analysis reveals, however, that the dichroism is caused by crystal field effects in the monolayer films, which is a non trivial effect because the high spin Ni $3d^{8}$ ground state is not split by low symmetry crystal fields. We present a practical experimental method for identifying the independent magnetic and crystal field contributions to the linear dichroic signal in spectra of NiO films with arbitrary thicknesses and lattice strains. Our findings are also directly relevant for high spin $3d^{5}$ and $3d^{3}$ systems such as LaFeO$_{3}$, Fe$_{2}$O$_{3}$, VO, LaCrO$_{3}$, Cr$_{2}$O$_{3}$, and Mn$^{4+}$ manganate thin films.